Newer Horizon of Mesenchymal Stem Cell–Based Therapy in the Management of SARS-CoV-2–Associated Mucormycosis: A Safe Hope for Future Medicine - Raghav, Alok; Ali, Syed Ghazanfar; Jeong, Goo-Bo; Gautam, Kirti Amresh; Banday, Shahid; Mateen, Qazi Noorul; Tripathi, Prashant; Giri, Richa; Agarwal, Saurabh; Singh, Manish; Khan, Haris M. (Frontiers in Microbiology, 2021)
SARS-CoV-2 infected patients have been reported to show immunocompromised behaviour that gives rise to a wide variety of complications due to impaired innate immune response, cytokine storm, thrombo-inflammation. Prolonged use of steroids, diabetes mellitus, and diabetic ketoacidosis (DKA) are some of the factors responsible for the growth of Mucorales in such immunocompromised patients, thus can lead to a life-threatening condition referred to as mucormycosis. Therefore an early diagnosis and cell based management in mucormycosis is need of the hour a must to help the affected patients to the overcome this severe condition. In addition, extended exposure to anti-fungal drugs/therapeutics has been found to initiate hormonal and neurological complications. More recently, mesenchymal stem cells (MSCs) have been used to exhibit immunomodulatory function and prove to be beneficial in clinical cell-based regenerative approach. The immunomodulation ability of MSCs in mucormycosis patient boosts the immunity by the release of chemotactic proteins. MSCs based therapy in mucormycosis along with the combination of short term anti-fungal drugs can be utilized as a prospective approach for mucormycosis treatment with promising outcomes. However, pre-clinical and clinical trials are needed to establish the precise mechanism of MSCs in mucormycosis treatment.